Upaya Pencegahan Penyalahgunaan Narkoba Dengan Peningkatan Kegiatan Kewirausahaan Keluarga di Desa Patumbak 1, Kabupaten Deli Serdang - Zulyadi, Rizkan; Munawir.S, Zaini; Utama, Amrin Mulia (Yayasan Daarul Huda Kruengmane, 2024)
The more advanced the times, the more negative things are present in society. This service activity was carried out in Patumbak Village 1, Patumbak District, Deli Serdang Regency. This village is located on a causeway so there is quite a lot of community traffic, so it does not rule out the possibility that many drug cases will be encountered in the community. because the large number of cases of delinquency among the younger generation has resulted in the rapid spread of drugs among society. Especially among students and students, drug abuse is of course very worrying. This is because they are the next generation of the nation. Therefore, it is necessary to have the participation of all parties to continue to socialize about the dangerous impacts of drug use both in terms of religion, health and law. The aim of this socialization and counseling is to provide understanding to the community, especially the younger generation, in this case the young generation in Patumbak 1 Village, Patumbak District, Deli Serdang Regency about the dangers of drug abuse by increasing family entrepreneurial activities not only from a legal perspective, but also through efforts instilling moral values in teenagers. The methods used are seminars, lectures, discussions and questions and answers. The activity participants are students and young people